Dejetos líquidos de suínos: escoamento superficial, alterações nos atributos químicos e físicos do solo e produtividade do feijão - Pessotto, Patrícia Pretto (2016)
The use of pig slurry as a source of nutrients for crops is a common practice in regions of pig production, however there is a growing concern about the risk of environmental contamination of soil and water as the continuous and excessive use of such waste. The purpose of this study was to evaluate losses of water, sediment and nutrients (N, P and Cu) through surface runoff and changes in chemical and physical attributes of a Red Oxisol under no-tillage system with continuous application of increasing doses of liquid pig manure (DLS) during the bean crop cycle. The study was conducted in an experimental area of the Federal University of Santa Maria campus Frederico Westphalen- RS, on a Red Oxisol, with a history of six years with DLS application. The treatments were: mineral fertilizer (NPK), organic fertilizer, consisting of DLS in doses of 25, 50, 75 and 100 m3 ha-1 and control without fertilization (0). Were evaluated surface runoff, loss of nutrients, chemical and physical properties of soil, productivity and crop yield components. The drained solution by natural rainfall was collected in gutters of 0.25 m2 installed in each plot, from October 2014 to January 2015. A sample of the drained volume was collected for measurement of sediment and concentrations of N, P and Cu present in the solution. Soil samples were collected for the determination of chemical parameters (N, P, K, Ca, Mg, Cu, Zn, MO, soil acidity indicators and total organic carbon) and physical parameters (aggregation, porosity and bulk density). The largest losses of soil, water and nutrients were observed from the beginning of sowing to the flowering of the culture, showing that little ground cover of the bean canopy is a determining factor for the runoff. Doses from 50 m3 h-1 DLS applied to the soil, associated with the application time, resulted in an increase of TOC content and enhance aggregation, porosity and density in the surface layer. The mineral fertilization of bean crops can be replaced by doses of DLS from 25 m3 ha-1, with no losses in maize productivity in an Red Oxisol clayey after six years of applying DLS.